More than just a Green Façade: Vertical Gardens as Active Air Conditioning Units. (2016) - Davis, M.J.M.; Ramirez, F.; Pérez, M.E.
Abstract: This paper explores the potential of a vertical garden to function as an active evaporative cooling air conditioning unit. It builds on previous work by Davis, Ramirez and Vallejo[1] . This study shows the results of a full scale, building incorporated vertical garden that measured 1.5 m wide by 2.8 m high. Air flowed behind the garden substrate, where it was cooled and humidified as it flowed down the back of the garden through its contact with the humid surface. The experimental results were compared to the mathematical model developed by Davis and Hirmer[2] . Overall, it was suspected that variations in ambient temperatures during the measurements taking process had a major influence on the results. In taking the data considered most reliable into account however, the results of the mathematical model end experimental data were within 0.44 °C. The results indicate that such gardens show great promise for building climate control, but where further research is needed in order to mitigate the influence of fluctuations in ambient temperatures.